1978
DOI: 10.1002/1097-0142(197803)41:3<957::aid-cncr2820410325>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Cryosurgery in the treatment of giant cell tumors of bone.A report of 52 consecutive cases

Abstract: Cryosurgery combined with routine "second look" biopsy has been previously reported in our initial series of 25 cases and has been demonstrated to be a promising modality in the treatment of giant cell tumors of bone. Further refinement of this surgical technique by more careful preliminary curettage has now significantly improved the rate of local tumor control and has markedly reduced the incidence of associated complications. While the problems of infection, fracture, delayed bone healing and local tumor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
9

Year Published

1979
1979
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(132 citation statements)
references
References 13 publications
3
120
0
9
Order By: Relevance
“…Despite low rates of recurrence, cryosurgery has not been widely adopted likely due its unfamiliarity and complication profile which includes postoperative fracture and skin necrosis/wound infection as high as 14 and 8 %, respectively [22,[40][41][42]. Marcove et al reported a recurrence rate of 17.6 % with curettage and the pouring of liquid nitrogen, which reduced to 4 % after a second cryosurgery [22].…”
Section: Cryosurgerymentioning
confidence: 99%
“…Despite low rates of recurrence, cryosurgery has not been widely adopted likely due its unfamiliarity and complication profile which includes postoperative fracture and skin necrosis/wound infection as high as 14 and 8 %, respectively [22,[40][41][42]. Marcove et al reported a recurrence rate of 17.6 % with curettage and the pouring of liquid nitrogen, which reduced to 4 % after a second cryosurgery [22].…”
Section: Cryosurgerymentioning
confidence: 99%
“…Cryothei'apy using liquid nitrogen has been used for the treatment of benign stage-2 (active), stage-3 (aggres sive) and low-grade malignant stage IA skeletal tumours.~ It is often advocated to avoid extensive [26][27][28][29][30] surgical destruction of tissue. * ' Intralesional resection is performed by curettage.…”
Section: Lowei Iccuucncc Latesmentioning
confidence: 99%
“…A common solution for this complication is to resect the whole segment of involved bone with the adjacent joint and reconstruct with an allograft, an implant or arthrodesis (Enneking 1983, Capanna et al 1990, Gitelis et al 1993, Muscolo et al 1993. Few reports of attempts to preserve the joint have been published (Marcove et al 1978, Malawer and Dunham 1987, Gitelis et al 1993, Meller 1993, Dreinhofer et al 1995. We describe our early experience and favorable results in 5 patients, using a new approach by a two-stage operation, the first for fracture reduction and union, the second for tumor eradication.…”
mentioning
confidence: 99%